2000
DOI: 10.1074/jbc.c000673200
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between G-protein and Protein Kinase C Modulation of N-type Calcium Channels Is Dependent on the G-protein β Subunit Isoform

Abstract: The modulation of N-type calcium current by protein kinases and G-proteins is a factor in the fine tuning of neurotransmitter release. We have previously shown that phosphorylation of threonine 422 in the ␣ 1B calcium channel domain I-II linker region resulted in a dramatic reduction in somatostatin receptor-mediated G-protein inhibition of the channels and that the I-II linker consequently serves as an integration center for cross-talk between protein kinase C (PKC) and G-proteins (Hamid, J., Nelson, D., Spae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…It has been proposed that phosphorylation by PKC of this threonine residue counteracts G␤␥ binding to the I-II linker and thus counters inhibitory modulation (Zamponi et al, 1997;Hamid et al, 1999). However, this was subsequently found only to hold true for G␤ 1 and not other G␤ subunits (Cooper et al, 2000). Furthermore, the sequence is not completely conserved in rabbit Ca V 2.2, which has alanine in place of threonine at the equivalent residue 422 (KRAAAKKSR in rabbit Ca V 2.2), although the same phenomenon of cross talk between G protein modulation and PKC activation occurs (Bertaso et al, 2003).…”
Section: E Basis For the Selectivity Of Calcium Current Inhibition Bmentioning
confidence: 91%
“…It has been proposed that phosphorylation by PKC of this threonine residue counteracts G␤␥ binding to the I-II linker and thus counters inhibitory modulation (Zamponi et al, 1997;Hamid et al, 1999). However, this was subsequently found only to hold true for G␤ 1 and not other G␤ subunits (Cooper et al, 2000). Furthermore, the sequence is not completely conserved in rabbit Ca V 2.2, which has alanine in place of threonine at the equivalent residue 422 (KRAAAKKSR in rabbit Ca V 2.2), although the same phenomenon of cross talk between G protein modulation and PKC activation occurs (Bertaso et al, 2003).…”
Section: E Basis For the Selectivity Of Calcium Current Inhibition Bmentioning
confidence: 91%
“…109,110 Of note, phosphorylation of Thr 422 only disrupts inhibition mediated by Gβ 1 , but not other Gβ subunits. 111 Thus the with Gβγ demonstrated by the Yue group. 122 Moreover, Agler et al 122 also demonstrated another role for the N-terminus: residues 56-95 directly bind to the N-terminal one-third of the I-II linker (from Ca V 2.2 but not Ca V 1.2).…”
Section: Differential Voltage-dependent Inhibition Within the Ca V 2 mentioning
confidence: 99%
“…5, B and C). The ability of PKC to antagonize G␤␥-mediated inhibition depends on the G protein ␤ subunit isoform, with only G␤ 1 being capable of sensing PKC-dependent phosphorylation of the channel (Cooper et al, 2000) (Fig. 5B).…”
Section: A Cross-talk Between G Protein Inhibition and Protein Kinasmentioning
confidence: 99%